MODEL FAKTOR FUNDAMENTAL PENENTU KEBIJAKAN DIVIDEN PADA PERUSAHAAN ASING DAN DOMESTIK YANG GO PUBLIK DI BURSA EFEK INDONESIA - Tatiek Nurhayati; Elfadien Sabita (Faculty of Economics and Business Universitas Jenderal Soedirman, 2011)
The phenomenon that occurred in the Indonesia Stock Exchange showed that investors have a primary goal in invest their funds into a company that is looking for income or investment return rate either form of dividend income and income from the difference between the selling price of stock over the purchase price (capital gains). For example, viewed from the status of his company, the company divided into 2 (two) categories, namely domestic and foreign ownership. With the difference in ownership status, the differences in character and culture of each investor will affect the company's performance through management policies were implemented. Seeing the reality that occurred in the Indonesia Stock Exchange turned out to be a percentage of domestic companies that pay dividends more than foreign companies. Seeing the difference is so interesting to do research about the factors that influence dividend policy. The population used in this study are all companies included in the group of foreign and domestic firms (based on the classification of the Indonesia Stock Exchange visits of company status) that have been going public in Indonesian Capital Market until the end of 2009. Samples taken for this study were 26 companies that meet the criteria of the sample that is comprised of 5 companies and 21 foreign domestic investment company. To determine the number of samples taken is to use a purposive sampling method. The analytical tool used is the classical assumption test and multiple regression. The results of this study is the only current ratio and growth variables that simultaneously affect the dividend payout ratio after further tests conducted by Stepwise method. While the partial growth and current ratio affect the dividend payout ratio. Together variable current ratio and growth contributed 22.7% in explaining the dividend payout ratio. And different test result that foreign firms have an average dividend higher than domestic companies. From these results, the management may consider the return on investment, current ratio, debt to total assets and growth as a predictor for determining the dividend payout ratio.